Strategies to develop english writing skills to a1 hearing-impaired students grade of península de Santa Elena high school, La Libertad – province of Santa Elena, school year 2021 – 2022 - Bohórquez Franco, Jennifer Elizabeth (2021)
The present project is an investigation which has as purpose to demonstrate the importance and useful of visual scaffolding as strategy for teaching English to hearing-impaired students. This is a way to promote the active participation of students within the learning process of English language. Moreover, this project contributes to the integral academic development of students with hearing impairment in order to develop their writing skills. The descriptive quantitative method allowed to stablish the necessary theory to develop the investigation for the benefit of 19 students with hearing problems from Península de Santa Elena high school with the purpose of reaching an A1 English level through a methodological guideline based on visual scaffolding strategy.